Establishment of a repeated social defeat stress model in female mice. Issue 1 (December 2017) - Takahashi, Aki; Chung, Jia-Ru; Zhang, Song; Zhang, Hongxing; Grossman, Yael; Aleyasin, Hossein; Flanigan, Meghan; Pfau, Madeline; Menard, Caroline; Dumitriu, Dani; Hodes, Georgia; McEwen, Bruce; et al.
Abstract Numerous studies have employed repeated social defeat stress (RSDS) to study the neurobiological mechanisms of depression in rodents. An important limitation of RSDS studies to date is that they have been conducted exclusively in male mice due to the difficulty of initiating attack behavior directed toward female mice. Here, we establish a female mouse model of RSDS by inducing male aggression toward females through chemogenetic activation of the ventrolateral subdivision of the ventromedial hypothalamus (VMHvl). We demonstrate that females susceptible to RSDS display social avoidance, anxiety-like behavior, reduction of body weight, and elevated levels of circulating interleukin 6. In contrast, a subset of mice we term resilient only display anxiety-like behaviors after RSDS. This model allows for investigation of sex differences in the neurobiological mechanisms of defeat‒induced depression‒like behaviors. A robust female social defeat model is a critical first step in the identification and development of novel therapeutic compounds to treat depression and anxiety disorders in women.